The hydrodynamic forces on a circular cylinder in proximity to a wall with intermittent contact in steady current. (1st December 2017) - Tong, Feifei; Cheng, Liang; An, Hongwei; Griffiths, Terry
Abstract: We present a three-dimensional Large Eddy Simulations (LES) study on the hydrodynamics of a circular cylinder close to a wall. Intermittent gaps between the cylinder and wall, forming spanning and non-spanning sections along the span are considered. This geometry setting represents an idealized model of pipelines laid on an uneven seabed. As compared to that of the corresponding spanwise-uniform cylinders, the drag coefficient on spanning sections is generally smaller, while the drag on non-spanning sections is slightly larger. Large amplitudes of the sectional forces are observed, partially due to the variations of the gap flow under the spanned sections. Flow deflection from the non-spanning section to the spanning section induces changes in local force and pressure distributions. Despite these changes, the mean force on the cylinder with intermittent contact as a whole is shown to be reasonably estimated by pro rata of forces from spanwise-uniform cylinders over the parameter space considered in this study. Highlights: The hydrodynamics of a circular cylinder with intermittent contact to a wall were studied. Spanwise difference brings distinct changes to sectional forces. The deflected flows aroundthe cylinder contribute greatly to local forces and pressure distributions. The total mean force can be estimated by pro rata of forces from spanwise-uniform cylinders.